Development of Character-Based Student Worksheets (LKPD) for Civic Education (PPKn) on Rights, Duties, and Responsibilities in Madrasah Ibtidaiyah - Mitha Syafira; Nur Rohman (Yayasan Zia Salsabila, 2025)
This study addresses the limited availability of instructional materials that explicitly integrate character education in civic education (PPKn) at the elementary level, particularly within the context of Islamic schools (Madrasah Ibtidaiyah). The primary aim of this research is to develop a student worksheet (LKPD) for PPKn that is based on character education and focused on the topic of rights, obligations, and responsibilities. Employing a qualitative approach with a research and development (R&D) design, the study was conducted at a Madrasah Ibtidaiyah in Kendari City. Data were collected through interviews, observations, and document analysis, involving teachers and students as key informants. The results indicate that the developed LKPD meets the criteria of validity, practicality, and effectiveness. It facilitates active student engagement and supports the internalization of core character values such as responsibility, empathy, and social awareness. The findings suggest that integrating character education through well-designed LKPDs can enhance both cognitive and affective learning outcomes in civic education. This research contributes to the development of character-based instructional tools and provides a practical model for educators aiming to cultivate civic virtues in early education settings.